Pengaruh Aplikasi Veson Imos terhadap Akurasi Review Pembayaran Kapal Gas di PT Pertamina International Shipping - Fralita Makitan; Taharuddin; Ansyar (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study was conducted to examine the extent to which the use of the Veson IMOS application and human resource factors influence the accuracy of gas vessel payment reviews at PT Pertamina International Shipping. A quantitative approach was employed involving 80 respondents selected based on predetermined research criteria. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics software. The findings indicate that the use of the Veson IMOS application has a positive and significant effect on the accuracy of gas vessel payment reviews, with a significance value of 0.003. Human resource factors were also found to have a positive and significant effect, with a significance value of less than 0.001. Furthermore, both variables simultaneously have a significant influence on the accuracy of payment reviews, as evidenced by the F-test significance value of less than 0.001. The coefficient of determination of 0.737 indicates that 73.7% of the variation in the accuracy of payment reviews can be explained by the use of the Veson IMOS application and human resource factors, while the remaining 26.3% is influenced by other factors beyond the scope of this study. Based on these findings, it can be concluded that the implementation of Veson IMOS and the quality of human resources play an important role in improving the accuracy of gas vessel payment reviews.